(untitled) (Triwikrama: Jurnal Ilmu Sosial, 2025)
Communication is a crucial aspect of social interaction in society and plays a vital role in building effective engagement, including within the context of children with special needs, such as those with Down Syndrome. This study aims to explore effective strategies and approaches for establishing communication with children with Down Syndrome, particularly during the initial stages of introduction and social relationship building within the community of the Association of Parents of Children with Down Syndrome (POTADS) in Surabaya. The research employs a qualitative method with a descriptive approach, involving direct observation and interviews with families and educators experienced in interacting with children with Down Syndrome. The findings reveal that successful early communication is significantly influenced by factors such as consistent use of nonverbal language, empathetic approaches, supportive communication environments, and a deep understanding of each child’s individual characteristics. The use of visual aids and positive reinforcement has been shown to enhance communication responses. These findings highlight the importance of communication training for parents, educators, and the broader community to foster inclusive and effective interactions with individuals with Down Syndrome. This research is expected to serve as a foundation for the development of sustainable adaptive communication models.